Previous SARS-CoV-2 Infection Status Among the Current RT-PCR-Positive Individuals Affected During the Second Wave of COVID-19 Infections in Chennai, India - Thangaraj, Jeromie Wesley Vivian; Kumar, Muthusamy Santhosh; Kumar, C. P. Girish; Yadav, Pragya; Rani, D. Sudha; Karunakaran, T.; Murhekar, Manoj (Frontiers in Public Health, 2022)
India witnessed a very strong second wave of COVID-19 during March and June 2021.Newly emerging variants of concern can escape immunity and cause reinfection. We tested newly diagnosed COVID-19 cases during the second wave in Chennai, India for presence of IgG antibodies to estimate the extent of re-infection. Of the 902 unvaccinated COVID-19 positive individuals, 53 (26.5%) were reactive for IgG antibodies and non-reactive for IgM antibodies. Among the 53 IgG positive individuals, interval between symptom onset (or last contact with known case in case of asymptomatic) was <5 days in 29 individuals, >=5 days in 11 individuals, while 13 asymptomatic individuals did not know their last contact with a positive case. Possible re-infections ranged between 3.2% and 4.3%. Our study findings indicate that re-infection was not a major concern. IgG sero-positivity among recently diagnosed unvaccinated COVID-19 could provide early indications about extent of re-infections in the area.